SIMULATION OF DOUBLE-PEAK RAINFALL PATTERNS DURING WET SEASON IN WESTERN JAVA DUE TO TOPOGRAPHY - Pradikta, Hafidz
Rainfall patterns in Western Java are generally categorized as monsoonal, characterized by a single peak in annual precipitation. However, some studies have identified a pattern with two peaks in precipitation per year in this region. The differences in these rainfall patterns may be attributed to variations in the number and distribution of observation stations, as well as the length of the data used, which may not adequately represent the extensive and complex topography. This study focuses on the role of topography in causing variations in rainfall patterns. To analyze the impact of topography, weather simulations were conducted with modified topography, where the topography of Western Java was removed. The aim of this simulation is to understand how changes in topography affect the distribution and intensity of rainfall in the region. Topography in Western Java plays a crucial role in shaping the double-peak rainfall pattern, particularly in the central region. The WRF simulation with removed topography (EXP) shows a reduction in the intensity of the double-peak rainfall pattern and a shift in the first peak. Moisture convergence analysis indicates that the removal of topography reduces the area of convergence, impacting the changes in annual rainfall patterns in the region.